2019
DOI: 10.9734/ajaees/2019/v32i430162
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Behavior and Constraints Faced by the Rose Growers

Abstract: The research study was conducted in Dharwad district during 2013-14, with a sample size of 120, farmers were randomly selected from three taluks viz, Hubli, Dharwad and Kalagatagi. The results revealed that 37.50 per cent of the respondents belonged to medium entrepreneurial behaviour category, whereas, 32.50 per cent and 30 per cent belonged to low and high entrepreneurial behaviour category respectively. Further, entrepreneurial behavioural characteristics such as innovativeness was medium (38.33%) in rose g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…The study revealed medium to high level of innovativeness was prevalent among the pig entrepreneurs due to the fact that majority of them were from middle age group (62.50%), had high level of formal education of graduation and above along with medium level of experience in pig farming. This is in conformity with Patel et al, (2014); Khode et al, (2018); Kulkarni & Jahagirdar (2019) who found majority of respondents in medium category of innovativeness, while it differs from that of Seth et al, (2012) who found majority of the respondents having high innovativeness.…”
Section: Resultssupporting
confidence: 83%
“…The study revealed medium to high level of innovativeness was prevalent among the pig entrepreneurs due to the fact that majority of them were from middle age group (62.50%), had high level of formal education of graduation and above along with medium level of experience in pig farming. This is in conformity with Patel et al, (2014); Khode et al, (2018); Kulkarni & Jahagirdar (2019) who found majority of respondents in medium category of innovativeness, while it differs from that of Seth et al, (2012) who found majority of the respondents having high innovativeness.…”
Section: Resultssupporting
confidence: 83%
“…Further it enhances the decision-making ability of youths. This finding is in accordance with the findings of Paisur et al, (2014); Kulkarni and Jahagirdar (2015); Manjunath (2015); Raina et al, (2016). The family type and family size was found positively and non-significantly related with entrepreneurial behaviour of respondents.…”
Section: Relationship Between Socio-economic Profile Of Youths and Th...supporting
confidence: 92%
“…The future advancement of the agricultural community hinges significantly on the entrepreneurial actions of farmers. Fruit crops have emerged as a promising avenue for entrepreneurial pursuits among farmers, offering higher yields and returns per unit area, optimizing resource utilization on farms, and presenting diverse opportunities for post-harvest processing and value addition [5][6][7].…”
Section: Introductionmentioning
confidence: 99%